1974
DOI: 10.1002/1097-0142(197402)33:2<527::aid-cncr2820330230>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Small cell carcinoma of the lung: Staging, paraneoplastic syndromes, treatment, and survival

Abstract: Thirty‐seven patients with small cell carcinoma of the lung were staged prior to therapy. The incidence of “extensive” or extrathoracic disease was 84%. Fourteen percent had CNS metastases. Bone marrow metastases were present in 47%. Laboratory and/or clinical evidence for a paraneoplastic syndrome was present in 26%. The majority of patients were treated with a three‐drug combination plus radiation therapy of the lung primary. Eighty‐eight percent of the patients treated with cyclophosphamide and vincristine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1
13

Year Published

1976
1976
1981
1981

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(35 citation statements)
references
References 10 publications
1
20
1
13
Order By: Relevance
“…Previously, chemotherapy for bronchial carcinoma has not been particularly effective but, more recently, several published series have shown that the prognosis for oat-cell carcinomas may be improved by the use of more radical combinations of radiotherapy and chemotherapy (Eagan et at., 1974;Johnson et al, 1976;Choi and Carey, 1976;Hornback et at., 1976 The cases in which both CEA and CT were measured revealed some interesting differences. The case of oat-cell carcinoma illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, chemotherapy for bronchial carcinoma has not been particularly effective but, more recently, several published series have shown that the prognosis for oat-cell carcinomas may be improved by the use of more radical combinations of radiotherapy and chemotherapy (Eagan et at., 1974;Johnson et al, 1976;Choi and Carey, 1976;Hornback et at., 1976 The cases in which both CEA and CT were measured revealed some interesting differences. The case of oat-cell carcinoma illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Particular value of such an approach can be anticipated in cases of oat-cell carcinoma, as these tumours are almost always disseminated at the time of presentation. There is, however, evidence to suggest that the prognosis may be improved by destruction of the main tumour masses by radiotherapy, and chemotherapy for presumed micrometastases (Horwitz et al, 1965;Eagan et al, 1974;Johnson, Brereton and Kent, 1976 (PTH) and calcitonin (CT).…”
mentioning
confidence: 99%
“…Bár a széles körű klinikai megfigyelések (2,3,6,7,13,14,15,20,36,37,42,69,70,72) és nagy anyagok statisz tikai értékelése (75) ezt az összefüggést egyre erő sebben alátámasztják, a végső bizonyíték még hiányzik, mert az állatkísérletek eredményei azt mutatták, hogy az oestrogeneknek és a progestogeneknek van daganatkeltő hatásuk patkányok és egerek májában (17), de csak az emberi anyagon alkalmazott dózis többszöröse volt hatásos.…”
Section: Megbeszélésunclassified
“…Ez világosan k itű n ik a cigánylakosság korfájáról (2) és létszám uk növekedési ü tem éből. A kedvező v álto zá st m in d en bizonnyal azon tényezők okozták, m ely ek az elm ú lt század végén a z eu ró p ai országokban is lehetővé te tté k a gyerm ek h alan d ó ság nagym érvű csökkenését; nevezetesen ,a szo ciális-k u l tu rális helyzet ja v u lá sa és hogy a kedvezőbb tá rs a d a l mi viszonyok m eg terem tették az egészségügyi v ív m á nyok kezdeti h aszn o sításán ak lehetőségét (7,8). A m á sodik ..m inőségi u g rást" je len m u n k án k b an m u ta tju k be és lényegében a XX.…”
Section: Szabolcs-szatmár Megyében Többségében 1958 éVtől áLlnak Renunclassified
See 1 more Smart Citation